Journal Notes - various authors (GDR Bulletin, 1984)
Reviews of: Sinn und Form Vol. 35, No. 2-3 (Wolfgang Ertl) Zeitschrift für Germanistik No. 3-4, 1982 (Karl-Heinz Schoeps) Neue Deutsche Literatur Vol. 31, No. 1-6 (Peter Beicken)